Caregivers can implement play‐based instruction without disrupting child preference. Issue 3 (13th May 2020) - Pisman, Maegan D.; Luczynski, Kevin C.
Abstract : Young children diagnosed with autism spectrum disorder often require systematic teaching to learn new skills, and caregivers can teach their children by embedding learning opportunities in a play‐based context. However, researchers have not evaluated procedures to train caregivers how to implement a combination of strategies designed to establish rapport and early language skills while maintaining play as a preferred context. Caregiver–child dyads composed of 2 mothers and their sons were recruited to participate. A multiple‐probe design across strategies was used to demonstrate the efficacy of behavioral skills training on the mothers' integration of parallel play, child‐directed interaction, teaching requests (mands), and teaching labels (tacts). Both children acquired the target requests and labels as a function of their mothers' teaching. By assessing the children's preferences, we confirmed the teaching strategies did not decrease toy engagement or the value of playing with their mother. We obtained stimulus generalization of the mothers' implementation of the strategies from a clinic to their home and maintenance of mother and child performance across a month.